2022
DOI: 10.1002/bbb.2344
|View full text |Cite
|
Sign up to set email alerts
|

Production of bio‐polyurethane (BPU) foams from greenhouse/agricultural wastes, and their biodegradability

Abstract: The exploration of effective utilization of greenhouse wastes is challenging. This paper demonstrates a hydrothermal treatment approach involving the co‐liquefaction of greenhouse wastes with agricultural residue in a mixed solvent of water and ethanol in the presence of a base catalyst, to convert greenhouse wastes and corn stalk into bio‐oil/bio‐polyol at a very high yield of 57.2%, accompanied by a very low yield of solid residue. This bio‐oil (hydroxyl number: 305 mg KOH/g) was successfully used as bio‐pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, attempts have been made to produce biofilms from the proteins of insects reared on organic waste to overcome the competition with the market of plant- and animal-derived food products [ 207 ]. It is important to report that lab-scale experiments are ongoing to synthesize more biodegradable thermoset materials, starting from mixing agriculturally derived oils with traditional precursors of polyester-type PURs [ 166 , 208 , 209 , 210 , 211 ]. The advantage of these biodegradable materials is that they can be assimilated as a carbon source by environmental organisms or at dedicated composting sites without releasing microparticles and without the need to develop a specific biotechnology in an industrial setup.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, attempts have been made to produce biofilms from the proteins of insects reared on organic waste to overcome the competition with the market of plant- and animal-derived food products [ 207 ]. It is important to report that lab-scale experiments are ongoing to synthesize more biodegradable thermoset materials, starting from mixing agriculturally derived oils with traditional precursors of polyester-type PURs [ 166 , 208 , 209 , 210 , 211 ]. The advantage of these biodegradable materials is that they can be assimilated as a carbon source by environmental organisms or at dedicated composting sites without releasing microparticles and without the need to develop a specific biotechnology in an industrial setup.…”
Section: Perspectivesmentioning
confidence: 99%
“…It has been observed that the average density of bio-based PU foams formed from biomass liquefaction is between 20 and 125 kg/ m 3 . 25,43,44 All the prepared foams have low densities ranging from 36.5 to 118.0 kg/m 3 , allowing for the conservation of the raw materials. not positively correlated with their open cell contents.…”
Section: Effects Of Blowing Agentsmentioning
confidence: 99%
“…23,24 Among various PU foams, hydroponic PU foams are ranked in the top 17 best plant growing media for soilless cultivation. 25,26 As a synthetic organic medium, hydroponic PU foam has numerous overwhelming advantages over natural organic and inorganic materials. Specifically, PU polymer is chemically inert, and the nutrient solution can be simply modified to satisfy the specific plant requirements in many cases.…”
mentioning
confidence: 99%
See 2 more Smart Citations